1998
DOI: 10.1007/s002689900398
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Recurrence following Surgery for Crohn's Disease

Abstract: Many factors have been examined in an attempt to define groups at higher risk for recurrence or recrudescence of Crohn's disease. Among these factors are age and onset of disease, gender, site of disease, number of resections, symptomatic status at the time of surgery, length of small bowel resection, fistulizing versus obstructive forms of disease, proximal margin length, microscopic margin histology, strictureplasty, and number of sites of disease, as well as the presence of colonic only disease, the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 45 publications
1
32
0
4
Order By: Relevance
“…Therefore, anastomosis and strictureplasty can also be performed in macroscopically inflamed areas of bowel [12, 16]. Although inflamed bowel persists by using the strictureplasty technique, there is no higher rate of local recurrence [2]. This finding in our study is in agreement with the findings of other authors and studies.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, anastomosis and strictureplasty can also be performed in macroscopically inflamed areas of bowel [12, 16]. Although inflamed bowel persists by using the strictureplasty technique, there is no higher rate of local recurrence [2]. This finding in our study is in agreement with the findings of other authors and studies.…”
Section: Discussionsupporting
confidence: 83%
“…Strictureplasty and limited resections are likely to prevent short-bowel syndrome even if repeated surgical procedures are required in the future, due to recurrence of the disease. In many studies it has been shown that strictureplasty is not likely to induce more recurrences than resection of the stenosis [2]. Today there is almost complete agreement that strictureplasty is a valuable technique in the treatment of small bowel strictures caused by Crohn’s disease [3, 4, 5, 6, 7, 8], at least for fibrotic strictures [9].…”
Section: Introductionmentioning
confidence: 99%
“…There are conflicting data regarding the effect of microscopic disease at the resection margin [2]. However, given that Crohn's disease is a pan-intestinal disease, that it is focal in distribution, and that histological abnormalities have been demonstrated in segments of bowel which appear to be grossly normal, the significance of microscopic disease at the resection margin is questionable.…”
Section: Bowel Resectionmentioning
confidence: 89%
“…Several factors such as age, onset of disease, gender, site of disease, number of resections, symptomatic status at the time of surgery, length of small bowel resection, proximal margin length, microscopic margin histology, type of anastomosis, type of surgery, blood transfusions, family history, and prophylactic treatment, were investigated for their supposed in uence in this phenomenon 13 . In the advanced, stenotic phase of CD, patients frequently present with recurrent episodes of partial small bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%